2012
DOI: 10.1089/tmj.2012.0026
|View full text |Cite
|
Sign up to set email alerts
|

Reactions to a Remote-Controlled Video-Communication Robot in Seniors' Homes: A Pilot Study of Feasibility and Acceptance

Abstract: Objective: Remote telepresence provided by tele-operated robotics represents a new means for obtaining important health information, improving older adults' social and daily functioning and providing peace of mind to family members and caregivers who live remotely. In this study we tested the feasibility of use and acceptance of a remotely controlled robot with video-communication capability in independently living, cognitively intact older adults. Materials and Methods: A mobile remotely controlled robot with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
74
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(80 citation statements)
references
References 22 publications
(18 reference statements)
4
74
0
Order By: Relevance
“…19 Seelye et al conducted an assessment that was limited to the installation and set up of computer software, communications experience and driving experience. 20 In our evaluation, we assessed the clinical function of the robot by investigating its ability to detect hazards.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Seelye et al conducted an assessment that was limited to the installation and set up of computer software, communications experience and driving experience. 20 In our evaluation, we assessed the clinical function of the robot by investigating its ability to detect hazards.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 Potential loss of privacy was not a concern for our participants. Taken together, these results suggest that older adults are open to using robot technology and remote monitoring to enhance their health care, even though it might affect their privacy.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the main limitation of this study lies in the sample size, and more samples will provide more reliable results. Obviously, the qualitative research of small samples has also obtained interesting findings in previous related studies [83,84]. In subsequent studies, we should expand the scale of participants as much as possible.…”
Section: Discussionmentioning
confidence: 74%
“…In this study, the robot was well received not only by the older person but by his or her adult children. 3 The use case for home robots in elder assistance is still in development. This study showed that the barrier at this point is not simply acceptance or usability, but likely more related to other factors such as cost.…”
Section: Incorporating Usersmentioning
confidence: 99%